Identification of a coactivator that increases activation of transcription by serum response factor and GAL4-VP16 in vitro. - Zhu, H (1992)
We have identified an activity in HeLa cell nuclear extracts that increases activation of transcription in vitro by serum response factor (SRF). This coactivator activity, termed CoS, did not affect basal (TATA only) transcription. CoS initially fractionated with transcription factors TFIIE and -F but was further purified to separate it from both TFIIE and -F as well as any other general transcription factor activity. We found that CoS was not specific for SRF activation, since it also increased transcriptional activation by the chimeric GAL4-VP16 activator. Differences among CoS and recently identified coactivators are discussed.